Pengaruh Stabilitas Keuangan Dan Pengawasan Dewan Komisaris Independen Terhadap Fraudulent Financial Statement Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia - Melin Aridhea, Vicky Anjani; Zanaria, Yulita; Sari, Gustin Padwa (Universitas Muhammadiyah Metro, 2022)
Many factors cause fraudulent financial statements, including financial stability and ineffective supervision. The purpose of this study is to determine the effect of financial stability and supervision of the Board of Independent Commissioners on Fraudulent Financial Statements in mining companies listed on the Indonesia Stock Exchange. This research method is quantitative research which takes place on the Indonesia Stock Exchange. Collecting data through library research by searching for company financial statement data on the website www.idx.com which is the official website of the IDX. The data analysis technique in this study uses multiple linear regression with the help of the eviews 10 application. Based on the results of the study, it can be concluded as follows: Financial stability partially has a negative effect on fraudulent financial reporting in mining companies on the Indonesia Stock Exchange. The supervision of the Independent Board of Commissioners partially does not have a positive effect on fraudulent financial reporting in mining companies on the Indonesia Stock Exchange.